2008
DOI: 10.1007/s11110-009-9029-7
|View full text |Cite
|
Sign up to set email alerts
|

Vertical structure of the field of current velocities in the northwest part of the Black Sea based on the LADCP data for May 2004

Abstract: The profiles of absolute current velocity obtained by using a lowered acoustic doppler current profiler (LADCP) are presented. In the course of the BSERP-3 expedition, the measurements were carried out in the regions of the Rim Current, anticyclonic eddy, and northwest shelf. In the core of the Rim Current, a unidirectional motion of waters is traced in layers below the main pycnocline down to depths greater than 500 m. Its characteristic velocity can be as high as 0.08 m/sec. It is shown that the direct actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In particular, according to the LADCP data of Expedition 1 kinematic characteristics of the anticyclonic eddy [9] and the spatial scales of the current velocity field variability in the surrounding area were determined. [24] In the continental slope area a pronounced correlation of the vertical current velocity field structure with the vertical distribution of the conditional density is observed. Fig.…”
Section: Vertical Structure Of Current Velocity Fieldmentioning
confidence: 93%
See 3 more Smart Citations
“…In particular, according to the LADCP data of Expedition 1 kinematic characteristics of the anticyclonic eddy [9] and the spatial scales of the current velocity field variability in the surrounding area were determined. [24] In the continental slope area a pronounced correlation of the vertical current velocity field structure with the vertical distribution of the conditional density is observed. Fig.…”
Section: Vertical Structure Of Current Velocity Fieldmentioning
confidence: 93%
“…The maximum vertical shifts are registered near the core of the cold intermediate layer (CIL), where there is a break in the density gradient. " Maximal velocity shears, according to [14], are located in layers of 10 -25 m and 50 -300 m. The authors of the paper [24] showed that in the Black Sea, the mean profile of the vertical shears has two well-defined maxima in the layers of the seasonal thermocline/pycnocline and main halocline/pycnocline. Maximal vertical shear in the density contrast layer separating the Azov and Black Sea waters is observed in the southern part of the Kerch Strait [31].…”
Section: Vertical Shears Of Currentsmentioning
confidence: 98%
See 2 more Smart Citations
“…The Brunt-Väisälä frequency profile, the two components of the flow velocity and the eigenfunction of the fifteen-minute internal wave of the second mode are shown in Figure 4. The data of soundings of the LADCP (Lowered Acoustic Doppler Current Profiler) [29] are used.…”
Section: Deep-sea Part Of the Black Seamentioning
confidence: 99%